Tempo Tracking on Guru Ding Dong Transcript using Connected Component Labeling (CCL) Method - Dharmajaya, Gede Putra; Bayu Atmaja Darmawan, I Dewa Made (JELIKU (Jurnal Elektronik Ilmu Komputer Udayana); Vol 8 No 2 (2019): Jeliku Volume 8 No 2, November 2019DO - 10.24843/JLK.2019.v08.i02.p05, 2020)
Music notation is a system of writing musical expressions as outlined in the form of symbols in the form of numbers or blocks. Music notation is used to document the composer's work in the form of songs so that it can be used by the public. In Balinese culture there is also a musical notation called Guru Ding Dong's Notation. This study discusses the segmentation of guru ding dong transcript to determine the tempo of each notation using the Connected Component Labeling method and the rule-based method. CCL algorithm applies Graph theory, where all pixels in an area that have a relationship with obeying the rules of pixel proximity will become a new image. The image that can be processed by the CCL algorithm is a binary image. In addition, this study also uses the image preprocessing method for initial data processing, namely grayscaling and binarization. The system built for research uses the MATLAB 2017b application. The results of the test resulted in an accuracy of the successful identification of characters and the tempo of each notation of 82%, this is influenced by the preprocessing process where there is a lot of noise in the image.